2018
DOI: 10.1212/nxi.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of optic neuropathy in Behçet disease

Abstract: ObjectiveWe present the clinical profile, features, and neuroimaging findings of 25 patients with Behçet disease (BD), and optic neuropathy (ON), which has been rarely reported in BD.MethodsData from 5 university hospitals were retrospectively reviewed, and patients with BD and ON were evaluated. There were 2 groups: (1) those already diagnosed with BD when ON developed (BD→ON group) and (2) those diagnosed with BD during the evaluation of ON (ON→BD group).ResultsThere were 25 BD patients with ON (13 males). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Therefore, physician should look for characteristic burdens and changes in the disease (mucus membranes and skin efflorescence, joint pain, and other changes) and immunological analyzes that can lead to a diagnosis. Immunosuppressants should be given along with corticosteroids [63].…”
Section: Behçet Diseasementioning
confidence: 99%
“…Therefore, physician should look for characteristic burdens and changes in the disease (mucus membranes and skin efflorescence, joint pain, and other changes) and immunological analyzes that can lead to a diagnosis. Immunosuppressants should be given along with corticosteroids [63].…”
Section: Behçet Diseasementioning
confidence: 99%
“…About 45% develop a subacute optic neuritis in which pain is uncommon (20% of cases) with disc swelling. [76][77][78] In one series, relapse occurred in 20%, and two-thirds returned to normal acuity following treatment; the nadir acuity was the determinant of visual outcome following treatment. 77 Another one-third had other neurological features of the condition.…”
Section: Optic Neuropathymentioning
confidence: 97%
“…77 Another one-third had other neurological features of the condition. 78 Two papers using 3T MRI have shown that there is enhancement of the optic nerve sheath rather than the nerve itself, implying that the disorder is a perineuritis. 79 80…”
Section: Optic Neuropathymentioning
confidence: 99%
“…Optic neuropathy (ON), although considered a rare manifestation of Behcet´s disease, might actually be overshadowed by uveitis' complications. It can appear during the course of already known BD (and should be considered as part of the neuro-BD disease spectrum), or it can even be the first manifestation of the disease (BD should then be kept in mind as a differential diagnosis of optic neuropathy Behcet's Disease DOI: http://dx.doi.org /10.5772/intechopen.85265 in regions where its prevalence is high) [17]. The prognosis of BD-associated ON seems not to be as poor as the one of BD uveitis, with excellent response to the combination of corticosteroids and immunosuppressants and recovery as the rule [18,19].…”
Section: Ocular Diseasementioning
confidence: 99%